Differences in Serum Human Chorionic Gonadotropin Rise in Early Pregnancy by Race and Value at Presentation. Issue 3 (September 2016) - Barnhart, Kurt T.; Guo, Wensheng; Cary, Mark S.; Morse, Christopher B.; Chung, Karine; Takacs, Peter; Senapati, Suneeta; Sammel, Mary D.
Abstract : OBJECTIVE: To assess whether variation in serum human chorionic gonadotropin (hCG) measures, used to assess early gestation viability, are associated with differences in clinical presentation and patient factors. METHOD: This retrospective cohort study included 285 women with first-trimester pain and bleeding and a pregnancy of unknown location for whom a normal intrauterine pregnancy was ultimately confirmed. Serial samples were collected at three U.S. sites and hCG changes were analyzed for differences by race, ethnicity, and clinical factors. A nonlinear, mixed-effects regression model was used assuming a random subject shift in the time axis. RESULTS: The hCG rise in symptomatic women with ongoing intrauterine pregnancy differs by patient factors and level at presentation. The 2-day minimum (first percentile) rise in hCG was faster when presenting hCG values were low and slower when presenting hCG value was high. African American women had a faster hCG rise ( P <.001) compared with non–African American women. Variation in hCG curves was associated with prior miscarriage ( P =.014), presentation of bleeding ( P <.001), and pain ( P =.002). For initial hCG values of less than 1, 500, 1, 500–3, 000 and greater than 3, 000 milli-international units/mL, the predicted 2-day minimal (first percentile) rise was 49%, 40%, and 33%, respectively. CONCLUSION: The rise of hCG levels in women with viable intrauterine pregnancies and symptoms of potential pregnancy failure varies significantly by initial value. Changes in hCG rise related to race should not affect clinical care. To limit interruption of a potential desired intrauterine pregnancy, a more conservative "cutoff" (slower rise) is needed when hCG values are high. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, https://clinicaltrials.gov, NCT00194168. Abstract : The rise of human chorionic gonadotropin levels in women with viable intrauterine pregnancies and symptoms of potential pregnancy failure varies significantly by initial value.